Method for recycling valuable metal from waste ternary lithium ion battery by using eutectic solvent

By using low-eutectic solvent DES and oxalic acid solution, valuable metals are efficiently recovered from the positive electrode materials of waste ternary lithium-ion batteries, solving the problems of high energy consumption, serious pollution and low recovery rates in the existing technology, and achieving efficient recycling effects with green and environmental protection.

CN119876611APending Publication Date: 2025-04-25SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411856048.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art has problems of high energy consumption, serious pollution and low recovery rate when recycling waste ternary lithium-ion battery positive electrode materials, making it difficult to achieve efficient green and environmentally friendly recycling.

Method used

The eutectic solvent DES is used as the leaching agent to extract valuable metals from the cathode material of the used ternary lithium-ion battery, and efficient recycling of nickel, cobalt, manganese and lithium is achieved through the reaction of oxalic acid solution and saturated sodium carbonate solution.

Benefits of technology

The efficient recycling of valuable metals in the positive electrode materials of waste ternary lithium-ion batteries is achieved. The entire process is environmentally friendly, green and pollution-free. The separated eutectic solvent can be recycled, with a high recovery rate and full utilization of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876611A_ABST
    Figure CN119876611A_ABST
Patent Text Reader

Abstract

The invention discloses a method for recycling metal from a waste ternary lithium ion battery by using a deep eutectic solvent. The method comprises the following steps: placing a pretreated positive electrode material in a deep eutectic solvent consisting of an amide hydrogen bond acceptor and an organic acid hydrogen bond donor to leach valuable metals, and filtering to obtain a leachate and first filter residues; adding an oxalic acid solution into the leachate, and filtering to form nickel-cobalt-manganese oxalate co-precipitate and first filtrate; and adding a saturated sodium carbonate solution into the first filtrate, and filtering to obtain a lithium carbonate precipitate and a second filtrate. According to the method, the nickel-cobalt-manganese oxalate coprecipitate and the lithium carbonate precipitate are mixed and calcined to obtain the regenerated positive electrode material, the eutectic solvent-amide / organic acid system is adopted for leaching, the problems of high energy consumption and strong corrosivity caused by the traditional high-temperature roasting and strong acid treatment processes are solved, the eutectic solvent can be recycled, and the cost is reduced. The method is environment-friendly; the method is simple in step and high in recovery efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of resource treatment of electronic waste, the present invention relates to pyrometallurgy and hydrometallurgy processes in the metallurgical field, and relates to a method for green and efficient recovery of valuable metals from waste ternary lithium-ion battery positive electrode materials. Background Art

[0002] Lithium-ion batteries (LIBs) are composed of a positive electrode, a negative electrode, a separator, an organic electrolyte, and a battery shell. The main components of the positive electrode materials of ternary lithium-ion batteries currently sold on the market are LiNi x Co y Mn 1-x-y O2, etc. At present, the commonly used recycling methods are mainly divided into three types: pyrometallurgy, hydrometallurgy and direct utilization. Pyrometallurgy is used by many recycling companies because of its simple operation and high efficiency. However, pyrometallurgy requires a lot of energy consumption, and a large amount of waste gas, such as dioxins, is released during the combustion process, requiring additional purification equipment to suppress air pollution. Compared with pyrometallurgy, hydrometallurgy is widely used in many industries because of its low energy consumption and high recovery rate. However, hydrometallurgical treatment usually uses strong acids (such as sulfuric acid) and reducing agents (such as hydrogen peroxide) to leach metals in a low-valent state. This technology usually involves a complex pretreatment process, and strong acid reagents bring serious environmental problems. The direct regeneration process is a new type of non-destructive recycling technology, which refers to a method of directly collecting and recycling without destroying the original structure of the LIB positive electrode material. However, it is currently difficult to invest in industrial expansion and production, and it is difficult to ensure the quality of each batch of products due to the influence of impurities on the regeneration process. Therefore, it is urgent and necessary to develop an environmentally friendly and green recycling process for waste ternary lithium-ion battery positive electrode materials. Summary of the invention

[0003] The present invention discloses a green and efficient method for recovering valuable metals from waste ternary lithium-ion battery positive electrode materials, and its purpose is to overcome the shortcomings of the traditional method for treating waste ternary lithium-ion battery positive electrode materials. The present invention provides a method for extracting valuable metals from waste ternary lithium-ion battery positive electrode materials using a low eutectic solvent DES as a leaching agent, so as to achieve efficient recovery of valuable metals nickel, cobalt, manganese and lithium. Not only is the entire recovery process environmentally friendly and pollution-free, the separated low eutectic solvent can also be recycled, and the recovery rate is high, so that resources are fully utilized.

[0004] The technical solution of the present invention is specifically described as follows.

[0005] The present invention provides a method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent, comprising the following steps:

[0006] (1) placing the pretreated positive electrode material in a low eutectic solvent to leach valuable metals, and filtering after the leaching to obtain a leachate and a first filter residue; wherein: the low eutectic solvent is prepared by mixing an amide hydrogen bond acceptor HBA and an organic acid hydrogen bond donor HBD in the presence of water or in the absence of water under heating conditions to form a transparent and uniform liquid, and the organic acid hydrogen bond donor HBD is a C4-C6 organic acid;

[0007] (2) adding oxalic acid solution to the leachate for sufficient reaction, filtering after the reaction is completed to obtain nickel-cobalt-manganese oxalate coprecipitate and a first filtrate;

[0008] (3) adding a saturated sodium carbonate solution to the first filtrate to carry out a sufficient reaction, and filtering after the reaction is completed to obtain a lithium carbonate precipitate and a second filtrate.

[0009] In the present invention, in step (1), the pretreated positive electrode material is obtained by the following steps: first, the waste ternary lithium-ion battery is discharged, then manually disassembled to obtain the positive electrode material, then the positive electrode material is cut into small pieces and placed in a NaOH solution to remove the aluminum foil, and finally filtered, and the obtained solid sample is placed in a muffle furnace for heat treatment to remove impurities such as a binder (PVDF), conductive carbon and acetylene black.

[0010] In the present invention, the positive electrode material obtained by disassembling waste ternary lithium-ion batteries has the following composition of valuable metals in terms of mass percentage: Li 5.0%-10.0%, Ni 25.0%-35.0%, Co 10.0%-15.0%, and Mn 10.0%-20.0%.

[0011] In the present invention, in step (1), in the low eutectic solvent, the amide hydrogen bond acceptor HBA is at least one of caprolactam, acetamide, and acetanilide; and the organic acid hydrogen bond donor HBD is at least one of citric acid, tartaric acid, and ascorbic acid.

[0012] In the present invention, in step (1), in the low eutectic solvent, the molar ratio of the amide hydrogen bond acceptor HBA to the organic acid hydrogen bond donor HBD is 1:2 to 2:1.

[0013] In the present invention, in step (1), the ratio of the positive electrode material to the low eutectic solvent is 5:1 to 50:1 g / L, the leaching temperature is 70-90°C, and the leaching time is 2-5 hours. In a specific embodiment, the leaching temperature is 80°C.

[0014] In the present invention, in step (1), the low eutectic solvent DES is used as the leaching agent to fully leach the positive electrode material without generating substantially the first filter residue.

[0015] In the present invention, in step (2), the pH of the added oxalic acid solution is 1 to 2, and the reaction temperature is 50°C to 80°C.

[0016] In the present invention, in step (3), the second filtrate is returned to the leaching system in step (1) for recycling, and no waste liquid is discharged during the process.

[0017] The present invention further comprises step (4):

[0018] The first filter residue obtained in step (1), the nickel-cobalt-manganese oxalate coprecipitate obtained in step (2), and the lithium carbonate precipitate obtained in step (3) are mixed and calcined, and finally cooled naturally to room temperature to obtain a regenerated LiNi x Co y Mn 1-x-y O2 positive electrode material.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. The deep eutectic solvent-amide / organic acid system proposed in the present invention can realize the efficient recovery of valuable metals in the cathode materials of waste ternary lithium-ion batteries;

[0021] 2. Amide / organic acid system leaching, no need to provide additional reducing agent, and the reaction temperature is low, which greatly reduces energy consumption;

[0022] 3. The leached filtrate can be recycled after further separation and precipitation, and the precipitate can be used as a precursor for ternary batteries, reflecting the economic efficiency of the system;

[0023] 4. The method of the present invention is used to extract valuable metals from the positive electrode materials of waste ternary lithium-ion batteries, which can replace the high energy consumption and high corrosion problems caused by high-temperature roasting and strong acid treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in conjunction with examples, but the examples are not intended to limit the present invention. All similar methods and similar variations of the present invention should be included in the protection scope of the present invention.

[0026] In the embodiment, the waste ternary lithium-ion battery is a 523 battery; the method for disposing the waste ternary lithium battery is: placing it in a 5g / L NaCl solution to discharge for 48 hours, and then naturally air-drying it to prevent spontaneous combustion due to short circuit during disassembly.

[0027] Example 1

[0028] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0029] A certain amount of caprolactam and citric acid were weighed, mixed at 50°C, and stirred for 10 minutes to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of caprolactam to citric acid was 2:1.

[0030] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 80℃ and the speed was 500r / min. The reaction was continued for 4h and the positive electrode powder was fully stirred to dissolve in DES.

[0031] The mixed solution after the reaction was filtered, and there was almost no filter residue. According to the analysis by inductively coupled plasma atomic emission spectrometer, the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 98.9%, 97.1%, 99.2% and 96.5% respectively.

[0032] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 99.01%, 98.5%, 98.1% and 3.42%, respectively.

[0033] The filtrate was added with saturated sodium carbonate solution at 85°C and reacted for 2h. The solid-liquid separation was performed by centrifugation and the solid was dried. The phase analysis by X-ray diffractometer scanning was Li2CO3. The precipitation rates of nickel, cobalt, manganese and lithium were 0.58%, 0.72%, 0.68% and 97.22% respectively by inductively coupled plasma atomic emission spectrometer analysis.

[0034] Example 2

[0035] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0036] Weigh 4.52 g of caprolactam and 3.84 g of citric acid, add 10 mL of deionized water, mix at 50° C., and stir for 10 min to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of caprolactam to citric acid is 2:1.

[0037] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 80℃ and the speed was 500r / min. The reaction was continued for 4h and the positive electrode powder was fully stirred to dissolve in DES.

[0038] The mixed solution after the reaction was filtered, and there was almost no filter residue. According to the analysis by inductively coupled plasma atomic emission spectrometer, the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 92.9%, 91.1%, 93.2% and 90.5% respectively.

[0039] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 98.32%, 96.7%, 97.4% and 1.75%, respectively.

[0040] The filtrate was added with saturated sodium carbonate solution at 85°C and reacted for 2h. The solid-liquid separation was performed by centrifugation and the solid was dried. The phase analysis by X-ray diffractometer was Li2CO3. The precipitation rates of nickel, cobalt, manganese and lithium were 1.03%, 0.75%, 0.71% and 99.71% respectively by inductively coupled plasma atomic emission spectrometer.

[0041] Example 3

[0042] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0043] A certain amount of acetamide and citric acid were weighed, mixed at 50°C, and stirred for 10 minutes to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of acetamide to citric acid was 1:2.

[0044] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 80℃ and the speed was 500r / min. The reaction was continued for 4h and the positive electrode powder was fully stirred to dissolve in DES.

[0045] The mixed solution after the reaction was filtered, and there was almost no filter residue. Analysis by inductively coupled plasma atomic emission spectrometer showed that the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 96.9%, 95.79%, 98.04% and 95.58% respectively.

[0046] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 98.98%, 98.42%, 98.31% and 3.24%, respectively.

[0047] The filtrate was added with saturated sodium carbonate solution at 85°C and reacted for 2h. The solid-liquid separation was performed by centrifugation and the solid was dried. The phase analysis by X-ray diffractometer was Li2CO3. The precipitation rates of nickel, cobalt, manganese and lithium were 0.47%, 0.65%, 0.61% and 97.47% respectively by inductively coupled plasma atomic emission spectrometer.

[0048] Example 4

[0049] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0050] Weigh 3 g of acetamide and 4.8 g of citric acid, add 6 mL of deionized water, mix at 50° C., and stir for 10 min to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of acetamide to citric acid is 2:1.

[0051] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 80℃ and the speed was 500r / min. The reaction was continued for 4h and the positive electrode powder was fully stirred to dissolve in DES.

[0052] The mixed solution after the reaction was filtered, and there was almost no filter residue. According to the analysis by inductively coupled plasma atomic emission spectrometer, the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 91.55%, 90.87%, 95.13% and 90.24% respectively.

[0053] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 97.01%, 99.52%, 98.36% and 1.27%, respectively.

[0054] The filtrate was added with saturated sodium carbonate solution at 85°C and reacted for 2h. The solid-liquid separation was performed by centrifugation and the solid was dried. The phase analysis by X-ray diffractometer was Li2CO3. The precipitation rates of nickel, cobalt, manganese and lithium were 1.26%, 0.15%, 0.32% and 98.62% respectively by inductively coupled plasma atomic emission spectrometer.

[0055] Example 5

[0056] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0057] Weigh 3.39 g of caprolactam and 5.28 g of ascorbic acid, add 6 mL of deionized water, mix at 50° C., and stir for 10 min to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of caprolactam to ascorbic acid is 1:1.

[0058] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 85℃ and the speed was 500r / min. The reaction was continued for 4h and the positive electrode powder was fully stirred to dissolve in DES.

[0059] The mixed solution after the reaction was filtered, and there was almost no filter residue. According to the analysis by inductively coupled plasma atomic emission spectrometer, the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 93.57%, 92.13%, 91.24% and 90.85% respectively.

[0060] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 97.92%, 96.36%, 96.17% and 0.74%, respectively.

[0061] The filtrate was added with saturated sodium carbonate solution at 85°C and reacted for 2 hours. The solid-liquid separation was performed by centrifugation and the solid was dried. The phase analysis by X-ray diffractometer scanning was Li2CO3. The precipitation rates of nickel, cobalt, manganese and lithium were analyzed by inductively coupled plasma atomic emission spectrometer and were 1.02%, 0.85%, 0.73% and 99.16%, respectively.

[0062] Example 6

[0063] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0064] A certain amount of acetamide and ascorbic acid were weighed, mixed at 50°C, and stirred for 10 minutes to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of acetamide to ascorbic acid was 1:1.

[0065] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 85℃ and the speed was 500r / min. The reaction was continued for 3h and the positive electrode powder was fully stirred to dissolve in DES.

[0066] The mixed solution after the reaction was filtered, and there was almost no filter residue. According to the analysis by inductively coupled plasma atomic emission spectrometer, the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 98.59%, 95.26%, 95.83% and 97.37% respectively.

[0067] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 98.81%, 99.22%, 98.17% and 1.89%, respectively.

[0068] The filtrate was added with saturated sodium carbonate solution at 85°C, reacted for 2h, centrifuged for solid-liquid separation, dried the solid, and X-ray diffractometer scanning phase analysis showed that it was Li2CO3. Inductively coupled plasma atomic emission spectrometer analysis showed that the precipitation rates of nickel, cobalt, manganese, and lithium were 0.95%, 0.34%, 0.57%, and 98.97%, respectively.

[0069] Example 7

[0070] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0071] A certain amount of caprolactam and tartaric acid were weighed, mixed at 50°C, and stirred for 10 minutes to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of caprolactam to tartaric acid was 1:1.

[0072] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 85℃ and the speed was 500r / min. The reaction was continued for 3h and the positive electrode powder was fully stirred to dissolve in DES.

[0073] The mixed solution after the reaction was filtered, and there was almost no filter residue. Analysis by inductively coupled plasma atomic emission spectrometer showed that the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 93.59%, 92.25%, 92.53% and 94.90%, respectively.

[0074] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 92.11%, 94.35%, 91.10% and 1.28%, respectively.

[0075] The filtrate was added with saturated sodium carbonate solution at 85°C, reacted for 2 hours, centrifuged for solid-liquid separation, and dried for solid. X-ray diffractometer scanning phase analysis showed that it was Li2CO3. Inductively coupled plasma atomic emission spectrometer analysis showed that the precipitation rates of nickel, cobalt, manganese, and lithium were 0.92%, 0.66%, 0.74%, and 98.21%, respectively.

[0076] Comparative Example 1

[0077] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0078] Weigh 3.39 g of caprolactam and 5.4 g of lactic acid, add 6 mL of deionized water, mix at 50° C., and stir for 10 min to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of caprolactam to lactic acid is 1:2.

[0079] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 90℃ and the speed was 500r / min. The reaction was continued for 4h and the positive electrode powder was fully stirred to dissolve in DES.

[0080] The mixed solution after the reaction was filtered to produce a milky white precipitate. Analysis by inductively coupled plasma atomic emission spectrometer showed that the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 86.9%, 9.3%, 11.5% and 28.24%, respectively. Analysis by inductively coupled plasma atomic emission spectrometer showed that the precipitation rates of valuable metals lithium, nickel, cobalt and manganese in the filter residue were 9.31%, 88.54%, 85.30% and 70.45%, respectively.

[0081] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 98.98%, 98.42%, 98.31% and 3.24%, respectively.

[0082] The filtrate was added with saturated sodium carbonate solution at 85°C and reacted for 2h. The solid-liquid separation was performed by centrifugation and the solid was dried. The phase analysis by X-ray diffractometer was Li2CO3. The precipitation rates of nickel, cobalt, manganese and lithium were 0.47%, 0.65%, 0.61% and 97.47% respectively by inductively coupled plasma atomic emission spectrometer.

[0083] Comparative Example 2

[0084] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0085] Weigh 3.39 g of caprolactam and 3.78 g of oxalic acid, add 6 mL of deionized water, mix at 50° C., and stir for 10 min to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of caprolactam to oxalic acid is 1:1.

[0086] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 80℃ and the speed was 500r / min. The reaction was continued for 4h and the positive electrode powder was fully stirred to dissolve in DES.

[0087] The mixed liquor after the reaction was filtered to produce a gray filter residue. According to analysis by inductively coupled plasma atomic emission spectrometer, the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 75.56%, 1.03%, 1.31% and 5.13%, respectively, and the precipitation rates of valuable metals lithium, nickel, cobalt and manganese in the filter residue were 21.24%, 94.37%, 96.74% and 91.48%, respectively.

[0088] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 97.01%, 99.52%, 98.36% and 1.27%, respectively.

[0089] The filtrate was added with saturated sodium carbonate solution at 85°C and reacted for 2h. The solid-liquid separation was performed by centrifugation and the solid was dried. The phase analysis by X-ray diffractometer was Li2CO3. The precipitation rates of nickel, cobalt, manganese and lithium were 1.26%, 0.15%, 0.32% and 98.62% respectively by inductively coupled plasma atomic emission spectrometer.

[0090] Comparative Example 3

[0091] Disassemble the discharged waste ternary lithium-ion battery into positive electrode material, negative electrode material and steel sheet separator. Cut the positive electrode material into small pieces of 5cm×5cm and put them into a beaker. Add excess 1mol / L sodium hydroxide solution, react for 6 hours, filter and dry in an oven at 60℃. Place the dried positive electrode material in a muffle furnace and keep it at 550℃ for 4 hours to obtain the pretreated positive electrode material.

[0092] A certain amount of acetamide and lactic acid were weighed, mixed at 50°C, and stirred for 10 minutes to obtain a transparent and homogeneous low eutectic solvent DES, wherein the molar ratio of acetamide to lactic acid was 1:1.

[0093] The leaching experiment was carried out according to the addition ratio of 20g / L of the pretreated waste ternary lithium-ion positive electrode powder and the low eutectic solvent. 0.2g of the positive electrode powder was weighed and placed in a 10mL conical flask, and the conical flask was transferred to a constant temperature magnetic stirrer. The reaction conditions were set to 85℃ and the speed was 500r / min. The reaction was continued for 3h and the positive electrode powder was fully stirred to dissolve in DES.

[0094] The mixed liquid after the reaction was filtered to produce a brown-yellow precipitate. According to analysis by inductively coupled plasma atomic emission spectrometer, the leaching rates of valuable metals lithium, nickel, cobalt and manganese in the filtrate were 88.59%, 13.26%, 14.83% and 22.37%, respectively, and the precipitation rates of valuable metals lithium, nickel, cobalt and manganese in the slag were 8.41%, 80.92%, 79.48% and 74.55%.

[0095] Oxalic acid solution was added to the leaching solution, the pH value of the solution was adjusted to 1.5, the reaction temperature was 50°C, and the mixture was stirred for 30 min. The solution was filtered and the filtrate and residue were analyzed by inductively coupled plasma atomic emission spectrometry. At this time, the precipitation rates of nickel, cobalt, manganese and lithium were 97.92%, 96.36%, 96.17% and 0.74%, respectively.

[0096] The filtrate was added with saturated sodium carbonate solution at 85°C and reacted for 2 hours. The solid-liquid separation was performed by centrifugation and the solid was dried. The phase analysis by X-ray diffractometer scanning was Li2CO3. The precipitation rates of nickel, cobalt, manganese and lithium were analyzed by inductively coupled plasma atomic emission spectrometer and were 1.02%, 0.85%, 0.73% and 99.16%, respectively.

[0097] The test results of Examples 1 to 7 are shown in Table 1:

[0098] Table 1

[0099]

[0100]

[0101] In summary, the low eutectic solvent-amide / organic acid system proposed in the present invention is used to achieve gentle and efficient recovery of valuable metals in waste ternary lithium-ion battery positive electrode materials, thereby preparing ternary lithium-ion battery precursors. Not only is the entire recycling process environmentally friendly, green and pollution-free, the filtrate after filtration can also be recycled, and the recovery rate is high, so that resources are fully utilized. The entire reaction system does not need to add additional reducing agents, reducing environmental pollution caused by strong acids; the reaction temperature is low, reducing energy consumption. Therefore, the present invention has the advantages of high environmental benefits and economic benefits.

[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent, characterized in that: The following steps are involved: (1) placing the pretreated positive electrode material in a low eutectic solvent to leach valuable metals, and filtering after the leaching to obtain a leachate and a first filter residue; wherein: the low eutectic solvent is prepared by mixing an amide hydrogen bond acceptor HBA and an organic acid hydrogen bond donor HBD in the presence of water or in the absence of water under heating conditions to form a transparent and uniform liquid, and the organic acid hydrogen bond donor HBD is a C4-C6 organic acid; (2) adding oxalic acid solution to the leachate for sufficient reaction, filtering after the reaction is completed to obtain nickel-cobalt-manganese oxalate coprecipitate and a first filtrate; (3) adding a saturated sodium carbonate solution to the first filtrate to carry out a sufficient reaction, and filtering after the reaction is completed to obtain a lithium carbonate precipitate and a second filtrate.

2. The method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent according to claim 1, characterized in that: In step (1), the pretreated positive electrode material is obtained by the following steps: first, the waste ternary lithium-ion battery is discharged, then manually disassembled to obtain the positive electrode material, and then the positive electrode material is cut into small pieces and placed in a NaOH solution to remove the aluminum foil, and finally filtered, and the obtained solid sample is placed in a muffle furnace for heat treatment to remove impurities.

3. The method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent according to claim 2, characterized in that: In the positive electrode material disassembled from the waste ternary lithium-ion battery, the composition of valuable metals is as follows, calculated by mass percentage: Li 5.0%-10.0%, Ni 25.0%-35.0%, Co 10.0%-15.0%, Mn 15.0%-20.0%.

4. The method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent according to claim 1, characterized in that: In step (1), in the low eutectic solvent, the amide hydrogen bond acceptor HBA is at least one of caprolactam, acetamide, and acetanilide; and the organic acid hydrogen bond donor HBD is at least one of citric acid, tartaric acid, and ascorbic acid.

5. The method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent according to claim 1, characterized in that: In step (1), in the low eutectic solvent, the molar ratio of the amide hydrogen bond acceptor HBA to the organic acid hydrogen bond donor HBD is 1:2 to 2:

1.

6. The method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent according to claim 1, characterized in that: In step (1), the ratio of the positive electrode material to the low eutectic solvent is 5:1 to 50:1 g / L, the leaching temperature is 70-90° C., and the leaching time is 2-5 h.

7. The method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent according to claim 1, characterized in that: In step (2), oxalic acid solution is added to adjust the pH of the system to 1-2, the reaction temperature is 50°C-80°C, and the reaction time is 10 min-50 min.

8. The method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent according to claim 1, characterized in that: In step (3), the second filtrate is returned to the leaching system of step (1) for recycling, and no waste liquid is discharged during the process.

9. The method for recovering valuable metals from waste ternary lithium-ion batteries using a deep eutectic solvent according to claim 1, characterized in that: The method further comprises step (4): The nickel-cobalt-manganese oxalate coprecipitate obtained in step (2) and the lithium carbonate precipitate obtained in step (3) are mixed and calcined, and finally cooled naturally to room temperature to obtain regenerated LiNi x Co y Mn 1-x-y O2 positive electrode material.

Citation Information

Cited By

  • A treatment method for leaching germanium from germanium-doped waste optical fiber

    CN122522018A